EVALUATION OF POLICIES FOR THE ORGANIZATION AND DEVELOPMENT OF STREET VENDORS IN THE MINASA MAUPA MARKET, SOMBA OPU DISTRICT, GOWA DISTRICT - Nurul Azizah; Sulmiah Sulmiah; Asri Nur Aina (Universitas Negeri Makassar, 2026)
This research aims to determine the evaluation of policies for the arrangement and development of street vendors at Minasa Maupa Market, Somba Opu District, Gowa Regency. The policy implemented by the regional government aims to improve order, cleanliness and welfare of street vendors. This research uses a qualitative descriptive approach with in-depth interviews, observation and documentation methods. The research results show that the policy for structuring and coaching street vendors has not yet achieved good results in the sense that it has not had a positive impact on market order and cleanliness. Judging from the policy evaluation indicators, it is stated that five of the six indicators including Effectiveness, Efficiency, Coverage, Equity and Responsiveness are still in the poor category and have not been implemented well in achieving goals and success, while the Decree indicators are in the good category and have achieved success goals. . There are obstacles such as lack of policy outreach, lack of supporting facilities, and resistance from traders. Therefore, it is still necessary to evaluate policies to ensure the sustainability and effectiveness of the program.